Contemporary legal and ethical dilemmas raised by advancement in medicine, science and technology - Jahn Kassim, Puteri Nemie (LexisNexis, 2004)
The late twentieth century depicts medical practice as being technologically advance-orientated environment. These rapid developments in medicine, science and technology have awakened many moral and legal questions. The law is required to establish rights and responsibilities in this developing area but how far has the law managed to keep pace with advances in medicine and medical technology is a question to be answered. A host of legal problems have arisen from various medical processes such as in vitro fertilization, freezing of embryos, genetic engineering, organ transplant and artificial insemination. The court is faced with the daunting task to make decisions in these areas where there exist conflicts of moral, ethical and religious values. In many cases, the legal outcome may not always be the same as the ethical perspective as the law, being an instrument of social regulation, has a more intrusive or coercive function.